Analysis of Environmental Factors with Malaria Incidence in Mabodo Health Center - Yana Afrina; Mursid Rahardjo; Nurjazuli Nurjazuli (Universitas Aisyah Pringsewu, 2021)
Malaria is one of the health problems that occur in the world, especially in tropical and subtropical regions. Malaria is an infectious disease transmitted through the bite of the female Anopheles mosquito and symptoms felt by malaria sufferers in the form of fever, cold heat, anemia, and sweating. This study aims to analyze the influence of environmental factors with the incidence of malaria in the working area of Mabodo Health Center muna regency. This type of research is quantitative with case control study design. The total sample in this study was 88 respondents, with sampling techniques are total sampling and purposive sampling. The results showed that risk factors that have an influence on the incidence of malaria are the state of the walls (p value 0.004), bushes (p value 0.004), going out at night (p value 0.003), the habit of hanging clothes (p value 0.002), and using mosquito nets (p value 0.005). The incidence of malaria occurs in the working area of Mabodo Health Center, because of environmental factors that support so that malaria cases still occur in the area.Malaria salah satu masalah kesehatan yang terjadi di dunia terutama di wilayah tropis dan subtropis. Malaria merupakan penyakit menular yang ditularkan melalui gigitan nyamuk Anopheles betina dan gejala yang dirasakan penderita malaria berupa demam, panas dingin, anemia, serta berkeringat. Penelitian ini bertujuan untuk menganalisis pengaruh factor lingkungan dengan kejadian malaria di wilayah kerja Puskesmas Mabodo Kabupaten Muna. Jenis penelitian ini yaitu kuantitatif dengan desain case control study. Total sampel dalam penelitian ini sebanyak 88 responden, dengan tehnik pengambilan sampel yaitu total sampling dan purposive sampling. Hasil penelitian menunjukan bahwa factor lingkungan yang memiliki pengaruh terhadap kejadian malaria yaitu keadaan dinding (p value 0.004), semak-semak (p value 0.004), keluar rumah pada malam hari (p value 0.003), menggantung pakaian (p value 0.002), dan kebiasaan menggunakan kelambu (p value 0.005). Kejadian malaria yang terjadi di wilayah kerja Puskesmas Mabodo, karena adanya faktor lingkungan yang mendukung sehingga kasus malaria masih terjadi di daerah tersebut.